Mutagenic Potential of Bos taurus Papillomavirus Type 1 E6 Recombinant Protein: First Description - Araldi, Rodrigo Pinheiro; Mazzuchelli-De-Souza, Jacqueline; Modolo, Diego Grando; Souza, Edislane Barreiros De [UNESP]; Melo, Thatiana Corrêa De; Spadacci-Morena, Diva Denelle; Magnelli, Roberta Fiusa; Carvalho, Márcio Augusto Caldas Rocha De; De Sá Júnior, Paulo Luis; Carvalho, Rodrigo Franco De; Beçak, Willy; Stocco, Rita De Cassia (Hindawi, 2015)
Bovine papillomavirus (BPV) is considered a useful model to study HPV oncogenic process. BPV interacts with the host chromatin, resulting in DNA damage, which is attributed to E5, E6, and E7 viral oncoproteins activity. However, the oncogenic mechanisms of BPV E6 oncoprotein per se remain unknown. This study aimed to evaluate the mutagenic potential of Bos taurus papillomavirus type 1 (BPV-1) E6 recombinant oncoprotein by the cytokinesis-block micronucleus assay (CBMNA) and comet assay (CA). Peripheral blood samples of five calves were collected. Samples were subjected to molecular diagnosis, which did not reveal presence of BPV sequences. Samples were treated with 1 g/mL of BPV-1 E6 oncoprotein and 50 g/mL of cyclophosphamide (positive control). Negative controls were not submitted to any treatment. The samples were submitted to the CBMNA and CA. The results showed that BPV E6 oncoprotein induces clastogenesis per se, which is indicative of genomic instability. These results allowed better understanding the mechanism of cancer promotion associated with the BPV E6 oncoprotein and revealed that this oncoprotein can induce carcinogenesis per se. E6 recombinant oncoprotein has been suggested as a possible vaccine candidate. Results pointed out that BPV E6 recombinant oncoprotein modifications are required to use it as vaccine.